Strategic gender research contributes to policy change in Sub-Saharan Africa and South Asia. - CGIAR Research Program on Maize (2021)
MAIZE and WHEAT researchers, together with colleagues within and beyond, published findings based on gender-transformative research and methods with clear policy implications for three countries Ethiopia, Malawi and Tanzania and contributed to policy impacts and practices in Morocco. Researchers also influenced policy-making, with potentially longer-term social change impacts in Nepal and Zambia. From a CGIAR-internal perspective, researchers expanded the reach of gender-transformative research and proposed innovations in gender-intentional maize breeding in sub-Saharan Africa.